Early and late outcomes of bevacizumab plus chemotherapy versus chemotherapy alone as a neoadjuvant treatment in HER2-negative nonmetastatic breast cancer: a meta-analysis of randomized controlled trials - Wei, Jinli; Luo, Yulin; Fu, Deyuan (OncoTargets and therapy, 2018)
To better clarify the efficacy of neoadjuvant bevacizumab plus chemotherapy (BEV + CT) vs chemotherapy (CT) alone in the treatment of HER2-negative nonmetastatic breast cancer. PubMed, Embase, Web of Science, and Cochrane Library databases were searched for relevant articles published from January 1, 2000 to July 31, 2018. Review Manager software version 5.3 was used to perform this meta-analysis. Six randomized controlled trials matched the selection criteria, yielding a total of 4,354 patients with early outcomes and 3,777 patients with late outcomes. Pooled pathological complete response (pCR) and 5-year disease-free survival (DFS) rates were higher for the neoadjuvant BEV + CT group (OR =1.37 [1.19, 1.58]; <0.001 and HR =0.84 [0.72, 0.98]; =0.020, respectively), but 5-year overall survival (OS) rate showed no significant difference (HR =0.79 [0.55, 1.11]; =0.180). Subgroup analysis showed that the pCR rate was significantly higher in both patients with hormone receptor (HR)-positive breast cancer (OR =1.30 [1.01, 1.66]; =0.040) and those with HR-negative breast cancer (OR =1.52 [1.25, 1.83]; <0.001) in BEV + CT group. Compared with CT alone, neoadjuvant BEV + CT significantly improved the 5-year DFS rate of HER2-negative breast cancer patients, but showed no benefit in terms of 5-year OS rate.